Isolated Hyperreligiosity in a Patient with Temporal Lobe Epilepsy - Garcia-Santibanez, Rocio (Case Rep Neurol Med, 2015)
A 40-year-old man with history of temporal lobe epilepsy presented to the emergency department with hyperreligiosity after medication noncompliance. After medications were resumed, he returned to baseline. Many famous prophets are believed to have suffered epilepsy. Waxman and Geschwind described a group of traits in patients with temporal lobe epilepsy consisting of hyperreligiosity, hypergraphia, altered sexual behavior, aggressiveness, preoccupation with details, and circumstantiality. The incidence of religious experiences ranges from 0.3 to 3.1 percent in patients with epilepsy. Religious experiences can be ictal, interictal, or postictal. Treatment is aimed at the underlying seizure etiology.